2020
DOI: 10.7759/cureus.10452
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Modeling in Saudi Arabia Using the Modified Susceptible-Exposed-Infectious-Recovered (SEIR) Model

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has created unprecedented healthcare emergencies across the globe. The World Health Organization (WHO) has proposed social distancing (SD) as a prudent measure to contain the pandemic and, hence, governments have been enacting lockdowns of varied nature. These lockdowns, causing economic and social strain, warrant the development of quantitative models to optimally manage the pandemic. Similarly, extensive testing aids in early detection and isolation, hence con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Thereafter, appropriate points of control measures were identified, and effective control measure values were chosen based on the pattern changes and in conjunction with the model fitting. The arrived pattern in the initial stage resembles the pattern proposed in the study of Ahmad [ 13 ]. Specifically, day 90 represents the toughest controls during the Eid 2020 vacation time, wherein there was complete lockdown in Saudi Arabia; this can also be seen from other aggregated indices provided by the OxCGRT (Figure 3 ).…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…Thereafter, appropriate points of control measures were identified, and effective control measure values were chosen based on the pattern changes and in conjunction with the model fitting. The arrived pattern in the initial stage resembles the pattern proposed in the study of Ahmad [ 13 ]. Specifically, day 90 represents the toughest controls during the Eid 2020 vacation time, wherein there was complete lockdown in Saudi Arabia; this can also be seen from other aggregated indices provided by the OxCGRT (Figure 3 ).…”
Section: Methodssupporting
confidence: 69%
“…The results from this scenario show that by the end of the pandemic, 76.32% of the population would get infected. These numbers are better than the previous study [ 13 ], as the general standard of well-being is being observed more rigorously and getting imbibed in the society in addition to robustness in the results due to this hybrid approach.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To simulate a pandemic or an epidemic, several models such as Susceptible-Infected-Recovered (SIR) [20] , [21] , [22] , [23] , [24] , Susceptible-Infected- Susceptible (SIS) [25] , Susceptible-Unidentified infected-Confirmed (SUC) [26] , Susceptible-Exposed-Infectious-Recovered (SEIR) [18] , [27] , Susceptible-Exposed-Infected-Quarantine-Recovered (SEIQR) [28] , Susceptible-Vaccinated-Infected-Recovered (SVIR) [29] , and Susceptible–Exposed–Infected–Recovered–Deceased (SEIRD) [30] have been applied. As most of the COVID-19 researchers base their analysis on the SIR [31] , [32] , [33] and SEIR [16] , [17] , [19] , [34] , [35] , [36] , [37] , this paper builds its pandemic model on these two models and demonstrates it in Fig. 1 .…”
Section: Coronavirus Spread and Adopted Policiesmentioning
confidence: 99%
“…These reports of this worldwide pandemic in Saudi Arabia are attributed to population size, resisted through strategic interventions and mitigation measures characterized by swift community action and hospital preparedness (3,10,26,(28)(29)(30)(31). This aligns with vision 2030 that positions the country as a business and tourism hub (8,32).…”
Section: Introductionmentioning
confidence: 98%